Wideband and Ultrawideband Channel Models in Working Machine Environment. (19th September 2012) - Taparugssanagorn, Attaphongse; Hämäläinen, Matti; Iinatti, Jari
Abstract : We present statistical models for wideband and ultrawideband (UWB) radio channels in a working machine cabin environment. Based on a set of measurements, it was found that such a small and confined space causes mostly diffuse multipath scattering rather than specular paths. The amplitude of the channel impulse responses in the wideband case is mostly Rayleigh distributed small-scale fading signal, with only a few paths exhibiting Ricean distributions, whereas the ones in the UWB case tend to be log-normally distributed. For the path amplitude, we suggest an exponential decay profile, which has a constant slope in dB scale, with the corresponding parameters for the UWB case. For the wideband case, a twofold exponential decay profile provides excellent fits to the measured data. It was also noted that the root-mean-square (RMS) delay spread is independent of the line-of-sight/obstructed line-of-sight situations of the channel. The multipath components contributing significant energy play a major role in such a small environment if compared to the direct path. In addition, the radio channel gains are attenuated with the presence of a driver inside the cabin.